The formal description of the quality data published on the Web: analysis of the Data Quality Vocabulary (DQV) - Jesus, Ananda Fernanda de [UNESP]; Segundo, Jose Eduardo Santarem [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2023)
The quality assessment process plays an important role in the reuse of data made available on the Web. To ensure the use and reuse of these data, it is necessary to formally describe them in a way that computational agents can understand. One of the possibilities to make this description viable is the Data Quality Vocabulary, elaborated by the World Wide Web Consortium. The objective was to verify the impact of the Data Quality Vocabulary in the process of formal description of the quality of data published on the Web, analyzing the objectives, characteristics, and structure of the vocabulary. The research has an exploratory and descriptive character, adopting as a method a study of the official documentation published by the consortium. As a result, an overview of the scenario that led to the development of the vocabulary was obtained, its structure was presented and its potential application was discussed. It is concluded that the Data Quality Vocabulary provides a general and customizable descriptive structure for providing the results of the data quality assessment process, which allows these results to be shared by its providers. It also allows the community to participate in the evaluation process and formally share the results obtained, thus reducing rework. It is also concluded that the vocabulary contributes to the reuse of data in the context of the Web by facilitating the use of automatic and semi-automatic tools in the evaluation and selection of data sources for the application.
Keywords: data quality; quality assessment; DQV